Sociocultural Determinants of Alcohol Abuse by Youths in Luanda Sub-county, Vihiga County, Kenya - Matara, Clifford M.; Winga, Maureen A. (European Scientific Journal, ESJ, 2021)
The WHO (2014a) indicates that 3.3 million deaths (5.9%) of all global deaths annually are attributable to alcohol abuse; with 5.1% of the global burden of disease and injury attributable to alcohol abuse. Alcohol is the most abused substance with the most affected persons being youth. In Kenya, prevalence of alcohol abuse by youths aged 18-35 years was 17.6% against the national average of the general populace which is at 13.6%. In the year 2017 Luanda sub-county recorded 635 reported cases of alcohol abuse with the administrators. Of the 635 reported cases in Luanda, 71 (11.18%) cases were of under 18 years, 192 (30.24%) were elderly (above 35 years) while 372 (58.58%) were aged 18-35 years. The objective of this study was to assess parental, peer, spousal and cultural influences of alcohol abuse by youths in Luanda Sub-county. A total of 422 respondents derived using Fischer’s formula were involved. Multi-stage sampling was done at sub-locations, villages and households to obtain respondents. Questionnaires featuring Audit tool score and Focus Group Discussions were used to collect data. Odds ratio with 95% confidence interval was employed to determine the likelihood of alcohol abuse. Qualitative data was analyzed using content analysis method. The socio-cultural factors associated with alcohol abuse were: parental alcohol use (p=0.000), peer influence (p =0.000), spousal alcohol use (p=0.035). The multivariate analysis showed significant association between alcohol abuse and spousal alcohol use (p=0.035 OR =0.462 [0.223 -0.955]), parental use of alcohol (p=0.000 OR=28.667 [15.516-52.965]) and peers (p=0.000 OR=10.012 [3.424-29.273]).